Occupational Health and Safety in the Mahabharata: An Ethical and Historical Perspective (International Journal of Occupational Safety and Health, 2025)
This paper examines how the guidelines of the Mahabharat, an epic, help to enrich Occupational Health and Safety (OHS) mechanisms in the modern context. This research examines the types of works and core ideas of OHS, including duty of care, prevention, and moral responsibility, as mentioned in the text. The study analyses risk factors and clear rules for safety and conduct. The paper answers how the work practices, safety systems, and moral laws in the Mahabharata can help improve OHS today. It explores the epic’s lessons on hazard prevention, mental resilience, and medical care, and examines their relevance in modern safety culture.The research compares the Mahabharata with current OHS concepts, focusing on safe work practices, preventive healthcare, mental readiness, and the role of moral duty (dharma). It also reveals safety principles found in the text that can be applied to enhance modern safety systems. It examines how the leaders in the workplace discharge their role and responsibilities to protect their team members. It focuses on how one can correlate one's duty with safety and mental strength to obtain success at work. It integrates ancient wisdom with modern science to support modern safety mechanisms. It also highlights the importance of moral values in improving safety culture, offering a more comprehensive approach to protecting health and dignity at work.